Handbook of thin-film deposition processes and techniques : principles, methods, equipment and applications - Seshan, Krishna (Materials science and process technology series. Electronic materials and process technology., 2002)
The 2nd edition contains new chapters on contamination and contamination control that describe the basics and the issues. Another new chapter on meteorology explains the growth of sophisticated, automatic tools capable of measuring thickness and spacing of sub-micron dimensions. The book also covers PVD, laser and e-beam assisted deposition, MBE, and ion beam methods to bring together physical vapor deposition techniques. Two entirely new areas are focused on: chemical mechanical polishing, which helps attain the flatness that is required by modern lithography methods, and new materials used for interconnect dielectric materials, specifically organic polyimide materials.